The Oxford companion to philosophy - Honderich, Ted (Oxford University Press, 1995)
Over 50 extended entries on the key areas of philosophy and the great philosophers 80 black and white portraits Almost 2,000 entries by 249 distinguished contributors 'The brave, large aim of this book,' writes Ted Honderich, 'is to bring philosophy together between two covers better than ever before. That is not a job for one man or one woman, or a few, or a team, although it is tried often enough. So 249 of us have joined forces.' The distinguished international assembly of philosophers who contribute to The Oxford Companion to Philosophy have succeeded in creating the most authoritative and engaging philosophical reference work in English. It gives clear and reliable guidance to all areas of philosophy and to the ideas of all notable philosophers from antiquity to the present day. The scope of the volume is not limited to English-language philosophy: it surveys the foremost philosophy from all parts of the world. The book's 2,000 alphabetically arranged entries, which cover everything from animal souls, arthritis in the thigh, and brain in a vat to Zoroastrianism and vague objects, are not only instructive but also entertaining: they combine learning, lucidity, elegance, and wit. There are more than fifty extended entries of 3,000 words on the main areas of philosophy and the great philosophers. These include: Alasdair MacIntyre on histories of moral philosophy Paul Feyerabend on the history of the philosophy of science Jaegwon Kim on problems of the philosophy of mind Ernest Sosa on problems of metaphysics Geoffrey Warnock on Berkeley Peter Singer on Hegel Anthony Kenny on Frege Anthony Quinton on philosophy itself The many fascinating shorter entries deal with...key concepts - personal identity, time, dualism doctrines - utilitarianism, holism, stoicism problems - the mind-body problem, the meaning of life schools of thought - Marxist philosophy, the Vienna Circle Practical issues - abortion, vegetarianism Individual thinkers past -Pythagoras, Confucius, Galileo, Goethe, Burke, Santayana, de Beauvoir, Radhakrishnan, Popper Individual thinkers present - over 150 contemporary figures, such as Davidson, Derrida, and Berlin are profiled. There are eighty black-and-white portraits of philosophers from the Greeks onwards, including some contemporaries. Interspersed throughout are short explanations of particular philosophical terms (qualia, supervenience, iff), puzzles (the Achilles paradox, the prisoner's dilemma), and curiosities (the philosopher's stone, slime). Each entry is accompanied by suggestions for further reading. A chronological chart of the history of philosophy is located at the end of the book, together with fifteen diagrams showing the structure of philosophy and the relations between its subjects and doctrines. This book will be an indispensable guide and a constant source of stimulation and enlightenment for anyone interested in abstract thought, the eternal questions, and the foundations of human understanding.